PENERAPAN METODE TALAQQI SAMA’ DALAM MENINGKATKAN KEMAMAMPUAN MEMBACA ALQURAN PADA MA’HAD TAHFIDZ ALABDIA THAILAND - Azhari Taringan, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This qualitative case study aims to describe the application of the talaqqi sama‘ method in improving Quranic reading skills at Ma'had Tahfidz Al-Abdia Thailand. Data were collected through participatory observation, in-depth interviews with teachers (musyrif) and students (santri), and documentation analysis. The results show that the learning interaction built through this method is direct, intensive, and communicative, allowing for optimal guidance and correction. The implementation follows systematic stages: listening (sama‘), imitation (talaqqi), correction (tashhih), and recitation (tasmi‘), emphasizing auditory-based learning and direct modeling from teacher to student. The talaqqi sama‘ method proved effective in improving students' Quranic reading skills, particularly in the accuracy of makhraj (articulation points), application of tajwid rules, reading fluency, and the formation of learning discipline and adab (ethics). This study confirms the relevance of classical Islamic learning methods in modern educational contexts and provides a practical model for Islamic boarding schools (ma'had) that wish to maintain the authenticity of Quranic transmission while improving reading skills.